ANALISIS PERBANDINGAN MANAJEMEN LABA PADA PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL DI INDONESIA - Vonny Santoso (Ma Chung Press, 2018)
The study aims to determine the influence of sharia status on earnings management in the banking company in Indonesia and the level of earnings management comparison between Islamic banks and conventional. This study was conducted on 28 banks and nine conventional existing Islamic banks in Indonesia. Data analysis technique used is multiple linear regression as well as two different test average (Independent sample T-test) with the help of SPSS 20 for Windows. The conclusion of this study is the status of the bank significantly influence the level of earnings management. Please also note if the level of earnings management in syariah-based bank is lower than conventional banks. The results of this study can be used as a material consideration corporate banking services in decision-making in action earnings management.